Social networks in education : survey on students at the International Islamic University Malaysia (IIUM). - Ramli, Alyaa Nadirah; Mohd Ghani, Asma' Salsabilla; Abdul Aziz, Famieza Azieta; Ahmad, Norhayati; Saidon, Norfaezah; Muhammad, Muhd. Rosydi (IIUM Press, 2011)
This study provides an analysis of the use of social networking sites in education. The primary objective is to identify opportunities and challenges in using social networking sites as medium to support teaching and learning process. Also, it discusses the awareness among the respondents towards using social networking in this context. Survey questionnaires were given to 32 respondents (Le. stUdents) from the International Islamic University Malaysia (IIUM). Finding informs that the respondents are positive towards using social networking sites in their educational activities. This is due to the fact that leT applications have great influence on the activities of society, particularly in education. Hence, social networking site can be introduced as a new educational tool for teaching and learning. It is hoped that this paper will help relevant educational agencies and institutions to be more creative and innovative in order to promote quality in education, particularly in Malaysia.